Analysis of entropy generation in micro-mini channel operated with nanofluids for turbulent flow / Nor Hidayahti Hasan @ Aminuddin - Nor Hidayahti , Hasan @ Aminuddin (2013)
With the advancement of nanotechnology, thermal science and thermal engineering, it is a high interest to develop the new generation of heat transfer fluids called nanofluid. Nanofluid as a new kind engineering material consisting of nanometer-sized additives and base fluids, offered compactness and high surface to volume ratio compared with conventional flow system. It has attracted great attention of researcher for its superior thermal properties and many potential applications. The superior thermal properties of nanofluids is the advantage to improve the thermal properties of base fluids used in many diverse industries including chemical engineering, electronics, transportation, microelectronics, aerospace and manufacturing. Second law of thermodynamic states that processes occur in a certain direction. During the energy convert from one form to another form, there is often degradation of the supplied energy into a less useful form. Entropy is refer to the less useful form of energy. The entropy generation or another term is irreversibility caused by factors friction, mixing of two fluids, unrestrained expansion, heat transfer across a finite temperature difference, electric resistance, inelastic deformation of solids and chemical reaction. Overview of the thesis is the analysis of entropy generation ratio and entropy generated by nanofluids caused by heat transfer and fluid friction flow in constant diameter of circular tube channel. The analysis conducted under the influences of volume fraction nanoparticles inside the nanofluids Cu-H2O, Al2O3-H2O, Cu-EG and Al2O3-EG. Also the analysis conducted under the influences of diameter size of circular tube channel. Entropy generation ratio decrease with increasing volume fraction nano particles in base fluids. Entropy generation ratio is decrease due to thermo-physical properties of nanofluids such as thermal conductivity, viscosity and density increase as volume fraction nano particles increase in base fluids. Entropy generation rate by heat transfer and fluid friction of nanofluids decrease as the volume fraction nano particles in the base fluids increase and decrease as the circular micro-mini channel diameter increase. Nano particles copper and alumina both effective according to the suitability with the thermo physical properties and size diameter of tube channels. Journal on the entropy generation due to heat transfer and flow have the findings which supported the thesis. However further research is required for better understanding of nanofluids. The thermo physical properties of nanofluids can be a function of parameters such as particle shape, particle agglomeration and particle polydispersity.In order to clarify these variables, a number of experiments will be necessary to be conducted. Due to the limitations of production preparation of nanofluids is a challenge to enhance the knowledge about nanofluids.